An Interesting Case of Atherosclerotic Occlusion of the First Septal Perforator in a Physically Young and Fit Individual Causing Complete Heart Block - Chahine, Johnny (Cureus, 2019)
Complete heart block (CHB) is an unfortunate complication of an anterior and inferior myocardial infarction (MI). We present a case of an atherosclerotic occlusion of the first septal perforator leading to CHB requiring permanent pacemaker placement in a young patient. A 33-year-old healthy white male presented to the emergency department with an episode of syncope. His vitals were stable, and his physical exam was unremarkable. His electrocardiogram (EKG) showed CHB and ST elevations in V1, V2, and V3 suggestive of septal MI. He underwent emergent left heart catheterization which revealed significant stenosis of the proximal left anterior descending (LAD) artery, proximal diagonal artery, and the first septal perforator. An intervention was done with stent placement in the LAD and insertion of a temporary pacemaker. After removal of the temporary pacemaker two days later, the patient developed asystole with alternating bundle branch block which prompted immediate reinsertion of the temporary pacemaker which was replaced later with a permanent pacemaker. The patient was stable afterward and discharged. The persistent atherosclerotic occlusion of the first septal perforator prevented adequate perfusion of the conduction system, even after revascularization of the proximal LAD. In conclusion, it is essential to acknowledge that difficulty to revascularize an occluded septal perforator raises the need for a permanent pacemaker to prevent a CHB.